Anda di halaman 1dari 46

Assignment 1 of MTH401 (Fall 2006)

Q.No:1 ( xy + 2 x + y + 2)dx + ( x 2 + 2 x)dy = 0 --------------(A)


Solution:
[ x( y + 2) + 1( y + 2)] dx + x( x + 2)dy = 0
( x + 1)( y + 2)dx + x( x + 2)dy = 0
x( x + 2)dy = −( x + 1)( y + 2)dx
dy ( x + 1)( y + 2)
=−
dx x( x + 2)
dy  x +1 
= − .( y + 2) − − − − − − − − − −(1)
dx  x( x + 2) 
dy
= h( x) x.g ( y )
dx
such that
( x + 1)
h( x ) = −
x( x + 2)
and
g ( y) = y + 2
Solving g ( y ) = 0
y+2=0
y = −2 − − − − − − − (a)
i.e. constant solution to the given (1).

For nonconstant solution, separating variables in Eq. (1)


dy  x +1 
= −  dx
y+2  x( x + 2) 
Integrating,
dy x +1
∫ y + 2 = −∫ x2 + 2 x dx
d ( y + 2) 1 (2 x + 2)
∫ ( y + 2) = − 2 ∫ x 2 + 2 x dx ∵ dy = d ( y + 2)
1 d ( x 2 + 2 x)
⇒ ln y + 2 = − ∫ 2
2 x + 2x
1
⇒ ln y + 2 = − ln x 2 + 2 x + c1 ∵ d ( x 2 + 2 x) = (2 x + 2)dx
2
−1
ln y + 2 = ln( x 2 + 2 x) 2
+ ln c2
As m ln y = ln ym
And c1 = ln c2 ( say )
ln y + 2 = ln ( x 2 + 2 x) c2 
−1
2
 

Taking antilog to base ‘e’ on both sides


−1
⇒ y + 2 = ( x 2 + 2 x) 2 c2
So, exact explicit form is
c
y= − 2 − − − − − −(b) where c2 = c ( say )
x2 + 2 x
Finally, combining both (a) & (b); so that solution (constant and
nonconstant) are
 c
y = −2
 x + 2x
2

 y = −2

Q.No:2
( x 2 + xy + y 2 )dx − x 2 dy = 0
Solution:
( x 2 + xy + y 2 )dx − x 2 dy = 0
⇒ ( x 2 + xy + y 2 )dx = x 2 dy
dy x 2 + xy + y 2
⇒ = = f ( x, y ) − − − − − − − (1)
dx x2
Replace tx → x and ty → y in (1)
dy t 2 x 2 + (tx)(ty ) + t 2 y 2
⇒ =
dx t 2 x2
t 2  x 2 + xy + y 2 
= 2 
t  x2 
= t 0 f ( x, y )
⇒ Given diff.eq is homogeneous of degree zero.
y
v=
x
dy d
⇒ = ( vx )
dx dx
dv
Put solution put =v+x
dx
dv x 2 + x(vx) + v 2 x 2
∴(1) ⇒ v + x =
dx x2
=1 + v + v 2
= f (1, v)
dv
v+x = 1 + v + v2
dx
dv
⇒ x = 1 + v 2 − − − − − − − (2)
dx
dv 1
(
= 1 + v2
dx x
)
= h( x).g (v)
Where,
1
h( x ) = and g (v) = 1 + v 2
x

For constant solution solving


For constant solution,
put g (v ) = 0
⇒ 1 + v2 = 0
⇒ v 2 = −1
⇒ v = ±i
y
= ±i
x
y = ± ix
Which are imaginary.

Now separating variables in (2) to find nonconstant solutions;


dv dx
∴ (2) ⇒ =
1+ v 2
x
On integrating ;
dv dx
∫ 1+ v 2
=∫
x
tan −1 v = ln x + c
v = tan [ ln x + c ]
y
= tan [ ln x + c ]
x
y = x tan [ ln x + c ]
i-e is the required real solution

Q.No:3
(2 x cos y + 3 x 2 y )dx + ( x3 − x 2 sin y − y )dy = 0 − − − − − (1)

Solution:
Here
M = 2 x cos y + 3x 2 y
∂M
⇒ = −2 x sin y + 3 x 2
∂y
N = x3 − x 2 sin y − y
∂N
= 3x 2 − 2 x sin y
∂x
∂M ∂N
∵ =
∂y ∂x
⇒ (1)is exact.
L.H.S. of (1) is an exact differential i.e. there exist a function f(x,y) s.t.
∂f
= 2 x cos y + 3x 2 y = M − − − − − −(2)
∂x
∂f
= x3 − x 2 sin y − y = N − − − − − −(3)
∂y
Integrating (2) w.r.t. ‘x’,we get
f ( x, y ) = ∫ 2 x cos y dx + ∫ 3 x 2 y dx + h( y )
Where h(y) is constant of integration w.r.t.’x’
f ( x, y ) = (2 cos y ).∫ xdx + (3 y ) ∫ x 2 dx + h( y )
= x 2 cos y + x3 y + h( y ) − − − − − −(4)
Now diff. w.r.t.’y’,we get
∂f
= − x 2 sin y + x3 + h′( y ) = N from (3)
∂y
= x3 − x 2 sin y + h′( y ) = x3 − x 2 sin y − y (Using value of N)
⇒ h′( y ) = − y
− y2
⇒ h( y ) =
2
So (2) required solution
y2
∴ f ( x, y ) = x 2 cos y + x3 y − =c
2

Alternate Method:

Here
M = 2 x cos y + 3 x 2 y
∂M
⇒ = −2 x sin y + 3 x 2
∂y
N = x3 − x 2 sin y − y
∂N
= 3x 2 − 2 x sin y
∂x
∂M ∂N
∵ =
∂y ∂x
⇒ (1)is exact.
Therefore diff.eq: has solution given by


y-Constant
Mdx + ∫ (terms of N not containing x)dy = c

{ Students remember above formula


for the solution of exact Differential equation}

∫ (2 x cos y + 3x y )dx + ∫ (− y )dy = c


2

y2
(2 cos y ) ∫ x dx + 3 y ∫ x 2 dx − =c
2
y2
x 2 cos y + yx3 − =c
2
Assignment 2 of MTH401 (Fall 2006)

Maximum Marks 30
Due Date 26 October
2006
Assignment Weight
age 2%

Question 1 marks
10

1
3
Check whether the differential equation y ' − y = x 4 y 3 either linear or bernoulli and also find its solution.
x
Solution:
1
3
y′ − y = x 4 y 3 − − − − − − − (1)
x
It is a non-linear, Bernoulli’s equation when compared with
y′ + P( x). y = Q( x). y n
Such that
3 1
P ( x) = − ; Q ( x) = x 4 ; n=
x 3
1
Dividing (1) by y 3 ; so
1
− 3 −1
(1) ⇒ y 3
y′ − y y 3 = x4
x
1
− 3 23
y 3
y′ −
y = x 4 − − − − − (2)
x
2 dv 2 − 13 dy
Put v = y 3 ⇒ = y
dx 3 dx
1
2 −
v′ = y 3 y ′ in (1)
3
1
3 −
v′ = y 3 y ′
2
3 3
v′ − v = x 4
2 x
2 2
⇒ v′ − v = x 4 − − − − − −(2)
x 3

i.e. linear diff.eq. in ‘v’ with


2 2
p( x) = − ; q( x) = x 4
x 3
So, integrating factor for (2) is
I .F . = e ∫
p ( x ) dx

2
∫ − x dx
=e
= e−2ln x
−2
= eln x
= x −2
1
= Multiplying it with eq.(2); such that it becomes exact.
x2
Therefore its solution is given by
v( I .F .) = ∫  q ( x) ( I .F ) dx + c
2
1 2 1
3
y . 2
= ∫ ( x 4 . 2 )dx + c
x 3 x
2
= ∫ x 2 dx + c
3
2 x3
= . +c
3 3
2
1 2
y 3 . 2 = x3 + c
x 9
2
2
⇒ y 3 = x5 + cx 2
9
2 3
y = ( x5 + cx 2 ) 2
9
Hence the result.
Question 2
marks 10

Find the orthogonal trajectories of the family of the curves y 2 = 4cx .


Solution:
y 2 = 4cx ---------- (A)
Diff. w.t.r. ‘x’; we get
dy
2y = 4c
dx
dy 2c
⇒ − − − − − −(1)
dx y
⇒ (1)eq for the orthogonal family.
dy 1
=−
dx 2c
y
y
=−
2c
dy y
=−
dx 2c
i.e. Seperable linear eq. So
dy 1
= − dx
y 2c
Integrating
dy 1
∫ y = − 2c ∫ dx
1
ln y = − x + D
2c
x
− +D
y=e 2c

x

=e 2c
.e D
x

⇒ y = Ae 2c − − − − − ( B)
Hence, family of curve ( A) are orthogonal to family ( B ).
Hence the result.
Question 3 marks 10

The population of a certain country is known to increase at a rate proportional to the number of
people presently living in the country. If after two years the population has doubled, and after
three years the population is 20,000, estimate the number of people initially living in the
country.

Solution:
Suppose that P0 is initial population of country and P(t), the population at any time ‘t’ then
population growth is governed by the diff.eq.

dP
= kP − − − − − (1)
dt
It ' s solution is
P(t ) = P0 ekt − − − − − (2)
According to given condition
P(2) = 2 P0
∴(2) ⇒ 2 P0 = P0 ekt
⇒ e2 k = 2
⇒ 2k = ln(2)
ln 2
⇒k =
2
0.693147
=
2
k = 0.3457
∴ (2) ⇒ P(t ) = P0 e(0.3457) t − − − −(3)
According to 2nd condition;
P(3) = 20, 000 Put in (3)
P(3) = P0 e(0.3457)(3)
20, 000 = P0 e1.03972
20, 000
P0 =
e1.03972
= 7071.07
P ≈ 7071
i.e. initial population of community.
Hence the result.
Assignment 3 of MTH401 (Fall 2006)

Maximum Marks 30
Due Date 11
November 2006
Assignment Weight
age 2%

Question 1 marks
10
Find the Wronskian of the functions;
xα Cos (2 ln x) & xα Sin(2 ln x).
Also find the values of ‘x’, for which above functions are linearly dependant and independent.
Solution:
Let
f1 = xα cos(2 ln x) and f 2 = xα sin(2 ln x)
f1' = α xα −1 cos(2 ln x) − 2 xα −1 sin(2 ln x) ; f 2' = α xα −1 sin(2 ln x) + 2 xα −1 cos(2 ln x)
= xα −1 [α cos(2 ln x) − 2sin(2 ln x) ] ; = xα −1 [α sin(2 ln x) + 2 cos(2 ln x) ]
f1 f2
Wronskian of both functions = W ( f1 , f 2 ) =
f1' f 2'
xα cos(2 ln x) xα sin(2 ln x)
=
xα −1 [α cos(2 ln x) − 2sin(2 ln x)] xα −1 [α sin(2 ln x) + 2 cos(2 ln x) ]
= x 2α −1 α sin(2 ln x) cos(2 ln x) + 2 cos 2 (2 ln x)  − x 2α −1 α sin(2 ln x) cos(2 ln x) − 2sin 2 (2 ln x) 
= 2x 2α −1

Linear InDependence:
As both f1 and f 2 are derivable on (−∞, ∞)
So their W ( f1 , f 2 ) ≠ 0
⇒ Their linear independence.
i.e. W ( f1 , f 2 ) ≠ 0
⇒ 2 x 2α −1 ≠ 0
x 2α −1 ≠ 0
x≠0
∴Functions are linear independent ∀ x ∈ R − {0}
Linear dependence:
Taking
C1 xα cos(2 ln x) + C2 xα sin(2 ln x) = 0 − − − − − (1)
C2 α
xα cos(2 ln x) = − x sin(2 ln x); C1 ≠ 0
C1
Both functions are linearly dependent if at least one C1 or C2 is not zero.
C2
Now (1) ⇒ − = Cot (2 ln x)
C1
C2
2 ln x = Cot −1 (− ) ∵C1 = 0
C1
1 C
ln x = Cot −1 (− 2 )
2 C1
1 C
Cot −1 ( − 2 )
x=e 2 C1

⇒ i.e. Exponential function and defined for all real numbers.


⇒ Functions are linear dependent ∀ x ∈ R.

Question 2
marks 10
Solve the IVP,
y′′′ + 7 y′′ + 19 y ′ + 13 y = 0; y (0) = 0, y′(0) = 2 & y′′(0) = −12
Solution:
Corresponding Auxiliary equation of differential equation is
m3 + 7 m 2 + 19m + 13 = 0
By inspection, we can see that m = -1 be its one root.
So using the Synthetic Division Method,
−11 7 19 13
0 −1 −6 − 13
1 6 13 0
Now, depressed equation is

m 2 + 6m + 13 = 0
−6 ± 36 − 52
m=
2
−6 ± −16
=
2
−6 ± 4i
=
2
m = −3 + 2i , − 3 − 2i
∴Solution is
y = C1e− x + e −3 x [C2 cos 2 x + C3 sin 2 x ] − − − − − (1)
Put 1st condition y (0) = 0 in (1)
∴ (1) ⇒ C1 + C2 = 0 − − − − − −(2)
Diff . eq.(2);
y′ = −C1e − x − 3e−2 x [C2 cos 2 x + C3 sin 2 x ] + e−3 x [ −2C2 sin 2 x + 2C3 cos 2 x ] − − − − − (3)
Put 2nd condition y / (0) = 12;
it ⇒ 2 = −C1 − 3 [C2 + 0] + [ 0 + 2C3 ]
− C1 − 3C2 + 2C3 = 2 − − − − − (4)
Differentiating (3) w.r.t ' x '
y′′ = C1e − x + 9e −3 x [C2 cos 2 x + C3 sin 2 x ] − 3e−3 x [ −2C2 sin 2 x + 2C3 cos 2 x ]
+ e−3 x [ −4C2 cos 2 x − 4C3 sin 2 x ] − 3e−3 x [ −2C2 sin 2 x + 2C3 cos 2 x ] − − − −(5)
Put 3rd conditon y // (0) = −12; we have
−12 = C1 + 9 [C2 ] − 3 [ 2C3 ] + [ −4C2 ] − 3 [ 2C3 ]
= C1 + 9C2 − 6C3 − 4C2 − 6C3
−12 = C1 + 5C2 − 12C3 − − − − − − − (6)
Solving eqs : (2), (4) & (6) simultaneously
we have;
C1 = 0; C2 = 0; C3 = 1
Eq.(1) ⇒ y = e−3 x sin 2 x i − e the required solution.
Question 3 marks 10

If the rate of spread of dengue virus is proportional to infected & non infected persons. Then
what will be number of infected persons after 2 weeks provided that a man carrying this virus,
come back to his community of 10000.Further it is provided that after one week, carriers
increase to 98.
Solution:
∵ a man carries dengue virus initially enter community
∴ x(0) = 1 {i − e no of carrier at t = 0}
Assuming no one leaves from community of 10,000.
So, initial value problem is
= kt (10,000 − t ) ;
dy
x(0) = 1
dt
i − e logistic equation when comparing with
dP
= P(a − bP) such that a = 10000k , b = k
dt
It ' s solution is given by
aP0
P(t ) = ; Here P0 = x(0) = 1
bP0 + ( a − bP0 ) e− at
So,
10,000k 10,000
x(t ) = −10,000 kt
= − − − − − (1)
k + 9999e 1 + 9999e−10,000kt
∵ it is given that after one week ,
number of carriers = 98 i − e
x(7) = 98
10000
∴(1) ⇒ 98 =
1 + 9999e−10,000(7 k )
98 + 98(9999e−70,000k ) = 10,000
10000 − 98
e−70,000k =
98 × 9999
Taking anti − log, we have
 10000 − 98 
− 70,000k ln(e) = ln  
 98 × 9999 
1  10000 − 98 
k =− ln  
70,000  98 × 9999 
k = 0.0000656388
10000
∴(1) ⇒ x(t ) = −10,000(0.0000656388)t
− − − −(2)
1 + 9999e
So for , after two weeks; no of carriers
Put t = 14 in (2)
x(14) ≅ 4947.98 ⇒ x(14) ≈ 4948
Assignment 4 of MTH401 (Fall 2006)

Maximum Marks 30
Due Date 11
November 2006
Assignment Weight
age 2%

Question 1 marks
10
Using the method of undetermined coefficient, find the appropriate form of particular
solution of differential equation;
y′ + 5 y = ( x + 1) Cosx + ( x −1) Sinx
.
Solution:
y′ + 5 y = ( x +1) Cosx + ( x −1) Sinx − − − −(1)
g ( x) = ( x −1)sin x + ( x + 1)cos x
Let g ( x) = g1 ( x) + g 2 ( x).
Here assumed solution for
g1 ( x) = ( x − 1) sin x is given as
( C1 x + C0 ) sin x + ( D1 x + D0 ) cos x − − − −(2)
and for
g 2 ( x) = ( x + 1) cos x is given as
( E1 x + E0 ) sin x + ( F1 x + F0 ) cos x − − − −(3)
∴ Combining (2) & (3) for R.H .S . of (1); we have particular solution as
y p = ( C1 x + C0 ) sin x + ( D1 x + D0 ) cos x  + ( E1 x + E0 ) sin x + ( F1 x + F0 ) cos x 
y p = ( C1 + E1 ) x + ( C0 + E0 )  sin x + ( D1 + F1 ) x + ( D0 + F0 )  cos x
y p = ( A1 x + A0 ) sin x + ( B1 x + B0 ) cos x
Where
Ai = Ci + Ei ; i = 0,1
B j = D j + Fj ; j = 0,1
Hence the result.

Question 2
marks 10
Solve
y′′ + y = Tan3 x .
By using method of variation of parameters.

Solution:
Associated auxiliary equation is
m2 + 1 = 0
⇒ m = ±i
⇒ yc = C1 cos x + C2 sin x
Here
y1 = cos x ; yc = sin x
cos x sin x
∴ W ( y1 , y2 ) =
− sin x cos x
= cos x + sin x
2 2

=1
Now
0 sin x sin 4 x
W1 = =−
tan 3 x cos x cos3 x
and
cos x 0 sin 3 x
W2 = =
− sin x tan 3 x cos 2 x
So
W1 sin 4 x W2 sin 3 x
u =
'
1 =− u ='
2 =−
W cos3 x W cos 2 x
sin 4 x sin 3 x
⇒ u1 = − ∫ dx ; ⇒ u2 = ∫ dx
cos3 x cos 2 x
= ∫ tan 2 x.sin x dx

= ∫ (sec 2 x − 1)sin x dx

= ∫ sec2 x.sin x dx − ∫ sin x dx


= ∫ sec x tan xdx + cos x
= sec x + cos x

∴ Re quired solution is
y = yc + y p
= C1 cos x + C2 sin x + y1 ( x) u1 ( x) + y2 ( x) u2 ( x)
 sin 4 x 
= C1 cos x + C2 sin x + cos x  − ∫ 3
dx  + sin x ( sec x + cos x )
 cos x 
Here u1 ( x) has very elongated approach for its solution.So it is not need to solve.

Hence the result.

However u1 is calculated as
Sin 4 x
u1 = − ∫ dx
Cos 3 x

= −∫
(1 − Cos 2 x )(1 − Cos 2 x )
dx
Cos 2 x .Cosx
= − ∫ ( Sec 2 x − 1) ( Secx − Cosx ) dx
= − ∫ ( Sec 3 x − Secx − Secx + Cosx )dx
= − ∫ Sec 3 xdx + 2 ∫ Secxdx − ∫ Cosxdx
= − ∫ Sec 3 xdx + 2ln Secx + Tanx − Sinx⋯⋯⋯ (1)
Now,
let I1 = ∫ Sec 3 xdx
= ∫ Sec 2 x .Secx dx

II . I
by int egration by patrs

= Secx.Tanx − ∫ Tanx.( Secx.Tanx )dx


= Secx.Tanx − ∫ Secx.Tan 2 xdx
= Secx.Tanx − ∫ Secx ( Sec 2 x − 1) dx
= SecxTanx − ∫ Sec 3 xdx + ∫ Secxdx
= SecxTanx − I1 + ln Secx + Tanx
2 I1 = SecxTanx + ln Secx + Tanx
1
I1 = SecxTanx + ln Secx + Tanx  − − − − Put in (1)
2
1
∴ u1 = −  SecxTanx + ln Secx + Tanx  + 2ln Secx + Tanx − Sinx + C
2
1 3
= − SecxTanx + ln Secx + Tanx − Sinx
2 2
Question 3 marks 10

Find the expression for the motion of the mass, provided that a mass of 2kg is suspended from
a spring with a known spring constant of 10N/m & allowed to come to rest under no air
resistance. It is then set in motion by giving an initial velocity of 150 cm/sec.

Solution:

Equation of motion is
k
x+
ɺɺ x=0 ∵ as motion goes under undamping & no air resistance.
m
d2x
∴ 2 + 5x = 0
dt
⇒ Its auxilary equation is
m2 + 5 = 0
⇒ m = ± 5i
∴ xc (t ) = A cos 5 t + B sin 5 t − − − − − − − −(1)
At t = 0 ; x(0) = 0
(1) ⇒ 0 = A
⇒ A=0
(1) ⇒ x(t ) = B sin 5 t − − − − − − − −(2)
Differentiating w.r.t. ' t '; we obtained
dx
v= = 5 B cos 5 t − − − − − − − −(3)
dt
At t = 0 ; v0 = v(0) = 150cm / sec
∴ (3) ⇒ 150 = 5 B
150
⇒B= = 0.6708
5
150
∴ (2) ⇒ x(t ) = sin 5 t
5
x(t ) = (0.6708) sin 5 t
i.e. e xpression for the motion.

Hence the result.


Assignment 5 of MTH401 (Fall 2006)

Maximum Marks 30
Due Date 30 December
22, 2006
Assignment Weight
age 2%

Question 1 marks
10
For the motion described by the harmonic oscillator having displacement at time‘t’ given by

Sin ( 6t + 1.816) ,
7
x(t ) =
6 find the first value of time for which the mass passes through
the equilibrium position heading downward.
Hint: Find the sign of velocity at different values of relevant t’s and then decide the
appropriate one.
Solution:

For spring mass system


x(t ) > 0 ⇒ downword direction of motion
and
x(t ) > 0 ⇒ equilibrium position of particle
7
⇒ sin(6t + 1.816) = 0
6
⇒ 6t + 1.816 = nπ ; n∈Z+
⇒ 6t1 + 1.816 = 1π , 6t2 + 1.816 = 2π ,......etc.
t1 = 0.2209, t2 = 0.7445,.........
Now
7
x(t ) = sin(6t + 1.816)
6
dx
= 7 cos(6t + 1.816)
dt
 dx 
∴   = 7 cos [ 6(0.2209) + 1.816] < 0
 dt  at t1
 dx 
 dt  = 7 cos [ 6(0.7445) + 1.816] > 0
at t2

 dx 
For the first time through equilibrium position, x → 0 from positive side and   > 0 at this position.
 dt 
 dx 
⇒   > 0 at t2 = 0.7445
 dt 
∴ required value of time = 0.7445
Hence the result.

Question 2
marks 10
For the harmonic oscillator under damped motion having position at time’t’given as
 2 
x(t ) = e−t  −2Cos3t − Sin3t  − − − −(1)
 3 
find the time when the graph of the solution (1) touches the graph of exponential function
± e −t .
Solution:
The graph of the solution
 2 
x(t ) = e− t  −2 cos 3t − sin 3t 
 3 
−t
touches the graph of ± e at those values of ' t ' for which
2
−2 cos 3t − sin 3t = ±1 ...........(1)
3
Taking L.H .S .
 
  2 
2
−2 − 
2  2   3 
−2 cos 3t − sin 3t = ( −2 ) +  −  cos 3t +
2
 sin 3t 
3  3 2 2

( −2 ) +  −  ( −2 ) +  − 
2 2 2 2 
  3  3 
 
2 10  −2  2 1 
=  cos 3t +  −  sin 3t 
3  2 10  3  2 10 
 3 3 
2 10  −3 1 
=  cos 3t − sin 3t 
3  10 10 
−3 1
Put sin φ = and cos φ = −
10 10
3
⇒ tan φ = =3
1
φ = tan −1 (3) = 1.25
2 2 10
∴ − 2 cos 3t − sin 3t = [sin φ .cos 3t + cos φ .sin 3t ]
3 3
2 10
= .sin [3t + φ ]
3
2 10
= sin [3t + 1.25]
3
2 10
∴ (1) ⇒ sin [3t + 1.25] = ±1
3
3
sin [ 3t + 1.25] = ±
2 10
 3 
3t + 1.25 = sin −1   + 2nπ
 2 10 
= 0.49 + 2nπ
2nπ − 0.755
t= ; n∈Z
3
. Hence the result.
Question 3 marks 10

Find the general solution of non-homogeneous Euler –Cauchy equation


x 2 y′′ + xy′ + 4 y = Sin ( ln x ) on the interval ( 0,∞ ) .Also discuss why solution of
above equation does not exist on the compliment of the interval ( 0,∞ ) .
Solution:
x 2 y′′ + xy′ + 4 y = Sin ( ln x ) ...........(1)
We rewrite the equation in the form

(x D
2 2
+ xD + 4 ) y = sin(ln x) .................(2) ; where D =
d
dx
Making transformation;
x = et
⇒ ln x = t ; ( x > 0)
 d 
∴ xDy = D′y , x 2 D 2 y = D′( D′ − 1) y ∵ D′ = 
 dt 
Then the given differential equation is transformed into the equation
D′ ( D′ − 1) y + D′y + 4 y = sin t
(D '2
+ 4 ) y = sin t ..............(3)
which is a differential equation coefficients.
∴ General solution of (3) is given by
y = yc + y p
where yc = c1 cos 2t + c2 sin 2t
For y p ;
y p = A cos t + B sin t
⇒ y 'p = − A sin t + B cos t ...............(4)
From (4);
∴ (3) ⇒ y ''p + 4 y p = sin t
⇒ ( − A cos t − B sin t ) + 4 ( A cos t + B sin t ) = sin t
⇒ 3cos t + 3B sin t = sin t
where from we obtain
3A = 0 , 3B = 1
1
⇒ A=0 ⇒B=
3
∴ General solution of (2) is
y = yc + y p
1
y = c1 cos(2 ln x) + c2 sin(2 ln x) + sin(ln x)
3
∵ the complement of ( 0, ∞ ) = ( −∞, 0] = Set of all non − positive real numbers
and the solution contain ln x which is not defined for Set of all non − positive real numbers
∴solution does not exists in the complement of ( 0, ∞ )
Assignment 6 of MTH401 (Fall 2006)

Maximum Marks 30
Due Date 05
January 2007
Assignment Weight
age 2%

Question 1
mark 05+05
(a) Discuss the validity of the recursive relation;
c +1 if n ∈ Evens
n
 2

cn =  1 if n ∈ Odds

 c3n−1 if n > 1 and n ∈ Odds , to become the coefficients of



the power series solution; ∑
n =o
cn x n of an ordinary differential equation (independent
variable’x’) by developing its corresponding sequence.
(b) Determine the singular points of the differential equation;
(x )
− 2 x 2 − 3x y′′ + x ( x − 3) y′ − ( x +1) y = 0
2 2
3

Hence classify these points under regularity and irregularity.


Solution: (a)
For given recursive relation
c + 1 if n ∈ Evens
 n2

cn =  1 if n ∈ Odds

 c3n−1 if n > 1 and n ∈Odds

Put n = 1, 2,3, 4,5,........to develop the progression :
n = 1 ⇒ c1 = 1
n = 2 ⇒ c2 = c 2 + 1 = c1 + 1 = 1 + 1 = 2
2

n = 3 ⇒ c3 = c3(3) −1 = c8 = c8 + 1 = c4 + 1
2

= (c 4 + 1) + 1 = c2 + 2 = 2 + 2 = 4
2

n = 4 ⇒ c4 = c 4 + 1 = c2 + 1 = 2 + 1 = 3
2

n = 5 ⇒ c5 = c3(5)−1 = c14 = c14 + 1 = c7 + 1


2

= c3(7) −1 + 1 = c20 + 1 = (c 20 + 1) + 1 = c10 + 2


2

c5 = (c10 + 1) + 2 = c5 + 3
2

⇒ c5 = c5 + 3
⇒ 0 = 3 i.e. false
⇒ recursive relation is invalid .
(b): For given differential equation

( x3 − 2 x 2 − 3 x)2 y′′ + x( x − 3) 2 y′ − ( x + 1) y = 0
x( x − 3) 2 ( x + 1)
⇒ y′′ + y′ − 3 y=0
( x − 2 x − 3 x)
3 2 2
( x − 2 x 2 − 3x) 2
x( x − 3) 2 ( x + 1)
y′′ + y′ − 2 y=0
x ( x − 3) ( x + 1)
2 2 2
x ( x − 3)2 ( x + 1)2
1 1
y′′ + y′ − 2 y = 0 .............(1)
x( x + 1) 2
x ( x − 3)2 ( x + 1)
Computing (1) with standard form i.e.
y′′ + P ( x) y′ + Q( x) y = 0
1 1
∴ P( x) = ; Q( x) = − 2
x( x + 1) 2
x ( x − 3) 2 ( x + 1)
Here s ingularities are
x = −1 ; x = 0 ; x = 3
For regularities and irregularities, we proceed as follows :
For x = −1
1
Taking ( x + 1) P( x) = .......(a )
x( x + 1)
−( x + 1)
( x + 1)2 Q( x) = 2 ...............(b)
x ( x − 3) 2
Here (a ) is analytic at x = −1 but (b) is not analytic.
⇒ x = −1 is irregular s ingularity.
For x = 0
1
xP( x) = i.e. analytic at x = 0
( x + 1) 2
−1
x 2Q ( x) = i.e. also analytic at x = 0
( x − 3) 2 ( x + 1)
⇒ x = 0 is regular s ingularity.
For x = 3
x −3
( x − 3) P ( x) = i.e. analytic at x = 3
x( x + 1) 2
−1
( x − 3) 2 Q( x) = 2 i.e. also analytic at x = 3
x ( x + 1)
⇒ x = 3 is regular s ingularity.
Hence tha result.

Question 2
marks 10
Using the power series method to find the general solution of the 2nd order homogeneous
differential equation
y′′ + y = 0 .

Solution:
Given differential equation is
y′′ + y = 0 ..........(1)
Assuimng that solution of given differential equation exists in the form
∞ ∞
y = ∑ cn x n = c0 + ∑ cn x n
n =0 n =1

So, term by term differentiation of the proposed series solution yields;


∞ ∞
y′ = ∑ ncn x n −1 = c1 + ∑ ncn x n −1
n =1 n=2

y′′ = ∑ n(n − 1)cn x n − 2
n=2
L.HS . of (1) ⇒
∞ ∞
y′′ + y = ∑ n(n − 1)cn x n −2 + ∑ cn x n + c0
n=2 n =1

Put k = n − 2; k = n such that k = 0,1, 2,....... in 1st and 2nd terms respectively;
∞ ∞
y′′ + y = ∑ (k + 1)(k + 2)ck +2 x k + ∑ ck x k
k =0 k =0

= ∑ [ (k + 1)(k + 2)ck + 2 + ck ] x k Put in (1);
k =0

∴ (1) ⇒ ∑ [ (k + 1)(k + 2)ck + 2 + ck ] x k = 0
k =0

∵ Set {x , x, x ,......, x , x
0 1 k k +1
,....} is linearly independent.
⇒ coefficient of x 0 , x, x1 ,......, x k , x k +1 ,.... are all zero.
⇒ for x k ; (k + 1)(k + 2)ck + 2 + ck = 0
ck
⇒ ck + 2 = − ; k = 0,1, 2,3,..........
(k + 1)(k + 2)
From iteration of this recurrence relation it follows that
c c
k = 0 ⇒ c2 = − 0 = − 0
1.2 2!
c c
k = 1 ⇒ c3 = − 1 = − 1
2.3 3!
c  c  1 (−1) 2 c0
k = 2 ⇒ c4 = − 2 = −  − 0  =
3.4  2!  3.4 4!
c3  c1  1 (−1)2 c1
k = 3 ⇒ c5 = − = − −  =
4.5  3!  4.5 5!
c4  (−1) 2 c0  1 (−1)3 c1
k = 4 ⇒ c6 = − = −  =
5.6  4!  5.6 6!
c  (−1) 2 c1  1 (−1)3 c1
k = 5 ⇒ c7 = − 5 = −   =
6.7  5!  6.7 7!
Above iteration leaves c0 and c1 arbitrary;
∴ required solution is given by
y = c0 + c1 x + c2 x 2 + c3 x3 + c4 x 4 + c5 x5 + c6 x 6 + c7 x 7 + ........
(−1)c0 2 (−1)c1 3 (−1)2 c0 4 (−1) 2 c0 2 (−1)3 c0 6 (−1)3 7
y = c0 + c1 x + x + x + x + c1 x + x + c1 x + ........
2! 3! 4! 5! 6! 7!
 x2 x4 x6   x3 x5 x 7 
= c0 1 − + − + ...... + c1  x − + − + ......
 2! 4! 6!   3! 5! 7! 
∴ By Maclaurin ' s series
x2 x4 x6
cos x = 1 − + − + ......
2! 4! 6!
x3 x 5 x 7
sin x = x − + − + ......
3! 5! 7!
∴ y = c0 cos x + c1 sin x
Hence the result.

Question 3 marks 10

In question ‘2’find the two linearly independent solutions by the Euler’s method
(The Auxiliary equation method).Also
(a) Compare this general solution with power series solution and discuss which method is
more general and why?
(b) Explain the linear independence of the two solutions.

Solution:
For differential equation
y′′ + y = 0 .........(1)
Put y = emx
⇒ y′ = memx
⇒ y′′ = m 2emx
∴⇒ (1) (m 2 + 1)e mx = 0
⇒ m2 + 1 = 0 (∵ emx ≠ 0 ∀ x ∈ R)
⇒ m = ±i
∴ required solution is given as
y = Aeix + Be− ix
= A [ cos x + i sin x ] + B [ cos x − i sin x ]
= ( A + B ) cos x + ( Ai − Bi ) sin x
y = C cos x + D sin x where C = A + B and D = i( A − B)
Here both solution of power series and by auxilary equations method are identical.
Power series method is more general than Euler ' s method because
it is applicable even when coefficients of { y′′, y′, y} are transcendantal functions,
but Euler ' s method holds for constant and polynomials coefficients.
(b) Linear Independence:
Here two solutions are
x2 x4 x6
y1 = 1 − + − + ................ = cos x
2! 4! 6!
x3 x5 x 7
y2 = x − + − + ................ = sin x
3! 5! 7!
For linear independance;
Put A cos x + B sin x = 0.................(a )
Differentiating ⇒ − A sin x + B cos x = 0 .........(b)
solving (a ) & (b) ⇒ A = B = 0
⇒ both solutions are linearly independent.
Hence the result.
Assignment 7 of MTH401 (Fall 2006)

Maximum Marks 30
Question 1
mark 05+05
Show that differential equation

 r ( x) y′′ +  q( x) + λ p( x)  y = 0 is equivalent to Legendre’s and Bessel’s differential


   
equation for suitable replacements of r ( x), p( x), q( x) and λ .
Hint: Differentiate first term of given differential equation and compare
r ( x), p( x), q( x) and λ for Legendre’s and Bessel’s equations.
Solution:
Given differential equation is
 r ( x) y′′ +  q( x) + λ p( x)  y = 0
   
⇒ r ( x) y′′ + r ′( x) y′ + [ q( x) + λ p( x)] y = 0...........(1)
∵ Legendre ' s equation is given as
(1 − x ) y′′ − 2 xy′ + n(n + 1) y = 0..............(2)
2

Comparing (1) & (2) for coefficients of y′′, y′ and y , we have


∴ r ( x) = 1 − x 2 ⇒ r ′( x) = −2 x
q( x) = 0 ; λ = n(n + 1) ; p ( x) = 1
∴ (2) ⇒ Legendre ' s equation is special case of (1)

Now, Bessel ' s equation is


x 2 y′′ + xy′ + ( x 2 − v 2 ) y = 0
  1 
∴ Dividing by x ⇒ xy′′ + y′ +  x +  −  v 2  y = 0 ..........(3)
  x 
Comparing (1) & (3) for coefficients of y ′′, y ′ and y , we have
1
r ( x) = x ⇒ r ′( x) = 1 ; q( x) = x ; p ( x) = −
; λ = v2
x
Hence Bessel ' s equation is also another special case of (1).

Question 2
marks 10
(a) For set of Legendre’s polynomials {Pn ( x); n = 0,1,2,3} ,verify that
1

∫−1 Pn ( x) Pm ( x) dx = 0, provided that m≠n

(b) Generate Legendre’s polynomials P4 ( x) and P5 ( x) using Rodrigue’s formula for


n = 4,5
Solution:
(a) As Legendre’s polynomials for r = 0,1, 2,3, 4,…… are given as
P0 ( x) = 1
P1 ( x) = x

P2 ( x) =
1
2
( 3x 2 − 1)
P3 ( x) = ( 5 x3 − 3 x )
1
2
Consider the case m ≠ n for 2,3 as 2 ≠ 3
1 1
∴ ∫ Pn ( x) Pm ( x) dx = ∫ P ( x) P ( x) dx
2 3
−1 −1
1

∫ 4 ( 3x − 1)( 5 x3 − 3 x ) dx
1
= 2

−1
1
=
1
4 −∫1
(15x5 − 9 x3 − 5x3 + 3x ) dx
1
1 15 6 9 4 5 4 3 2 
= x − x − x + x 
4  6 4 4 2  −1
1
= (0)
4
=0
Similarly, for all other cases like 0 ≠ 1,1 ≠ 2,3 ≠ 1 etc., we have
1

∫ Pn ( x) Pm ( x) dx = 0
−1
Hence verified.
(b)
∵ Rodrigues formula for Legendre ' s polynomials is
1 dn 2
. n ( x − 1) ...........(1)
n
Pn ( x) = n
2 n ! dx
Put n=4
1 d4 2
. 4 ( x − 1) ...........(2)
4
P4 ( x) = 4
2 4! dx
d4 2 d3  d 2 4
( ) ( x − 1) 
4
Here 4
x − 1 = 3 
dx dx  dx 
3
= 3  4 ( x 2 − 1) .2 x 
d 3

dx  
d3
=8  x ( x 6 − 3( x 2 )2 (1) + 3 x 2 (1) 2 − (1)3 ) 
dx3  
d3
= 8 3  x 7 − 3 x5 + 3 x3 − x 
dx
 
= 8 210 x 4 − 180 x 2 + 18  .............(3)
 It is obtained by taking three times the derivatives of x7 −3 x5 +3 x3 − x 
∴Put in (2) ⇒
1
P4 ( x) = .8  210 x 4 − 180 x 2 + 18
16.2 4
1
P4 ( x) = 35 x 4 − 30 x 2 + 3
8
Put n = 5 in (1);
1 d5 2
. 5 ( x − 1) ...........(4)
5
P5 ( x) = 5
2 5! dx
 By Binomial Theorm

( a − b ) = a − 5a b + 10a b − 10a b + 5ab − b
5 5 4 3 2 2 3 4 5

Here a = x 2 & b = 1

(x − 1) = x10 − 5 x8 + 10 x 6 − 10 x 4 + 5 x 2 − 1
2 5

d5 2 d 5 10
( )
5
∴ x − 1 =  x − 5 x8 + 10 x 6 − 10 x 4 + 5 x 2 − 1
dx5 dx 5 
= 30240 x5 − 33600 x3 + 7200 x
It is obtained by taking five times the derivatives of x10 −5 x8 +10 x6 −10 x4 +5 x2 −1
∴ Put in (4) ⇒
1
P5 ( x) = . 30240 x5 − 33600 x3 + 7200 x 
32.120
1
P5 ( x) = .480 63 x5 − 70 x3 + 15 x 
32.120
1
P5 ( x) = 63 x5 − 70 x3 + 15 x 
8
Hence the result.

Question 3 marks 10

Solve, if possible, the following differential equation by either systematic elimination or by use
of determinants:
( D +1) x + ( D −1) y = 2
3 x + ( D + 2 ) y = −1
Solution:
( D +1) x + ( D −1) y = 2 ..............(a)
3x + ( D + 2 ) y = −1 .............(b)
Multplying 3 with eq.(a)& ( D + 1) with eq.(b) then subtracting ;
3 ( D +1) x + 3( D −1) y = 6
3 ( D + 1) x + ( D + 1)( D + 2 ) y = ( D + 1) ( −1)
− − −
________________________________________________
3D − 3 − ( D 2 + 3D + 2 )  y = 6 + 1
 
3D − 3 − D − 3D − 2  y = 7
2

⇒ ( D 5 + 5 ) y = −7
d2y
⇒ + 5 y = −7..................(1)
dt 2
It ' s associated homogenous equation
d2y
+ 5 y = 0............(c) has solution
dt 2
y = emt
y′ = memt
y′′ = m 2emt
∴ (c) ⇒ ( m 2 + 5 ) e mt = 0
⇒ m2 + 5 = 0 ∵emt ≠ 0
⇒ m = ±i 5
∴For (1) ⇒ yc = c1 cos 5 t + c2 sin 5 t
Now assuimng
y p = A ⇒ y 'p = y ''p = 0
7
∴ (1) ⇒ 5 A = −7 ⇒ A=−
5
y = yc + y p
7
⇒ y (t ) = c1 cos 5 t + c2 sin 5 t − ..................(i )
5
For x(t ); Multplying ( D + 2 ) with eq.(a)& ( D − 1) with eq.(b) then subtracting ;
( D + 2)( D +1) x + ( D + 2)( D −1) y = ( D + 2) 2
3 ( D −1) x + ( D −1)( D + 2) y = ( D −1) ( −1)
− − −
________________________________________________
 D 2 + 3D + 2 − 3D + 3 x = 4 − 1
⇒ ( D 2 + 3) x = 3
d2x
⇒ + 3x = 3..................(2)
dt 2
It ' s auxilary equation associated to homogenous equation is
m2 + 3 = 0
⇒ m = ±i 3
xc = c3 cos 3 t + c4 sin 3 t
Assuming x p = B ⇒ x 'p = x ''p = 0
∴ (2) ⇒ 3B = 3
⇒ B =1
∴ x(t ) = xc + x p
⇒ x(t ) = c3 cos 3 t + c4 sin 3 t + 1..................(ii )
Hence, system (i ) & (ii ) give required solution of (a ) & (b).
Assignment 8 of MTH401 (Fall 2006)

Maximum Marks 30
Due Date
27January 2007
Assignment Weight
age 2%
Question 1
mark 05+05
Verify that the vector ‘ X ’ is the solution of the given system
dx
= 2x + y 1  4  t
where X =   et + 
dt
 te .
dy  3  −4 
= −x    
dt
Solution:
Given system is
dx
= 2x + y
dt
dy
= −x
dt
reducing the given system in matrix form
 dx 
 dt   2 1  x 
⇒ =
 dy   −1 0   y 
 dt 
d x  x 
⇒   = A 
dt  y   y
⇒ X ′ = AX .........(1) where assumig
 dx 
2 1  x(t )   x  d  x (t )   dt   x′(t )   x′ 
A=  ; X =  =  ; X ′ =  = = =
 −1 0  y (t )   y  dt  y (t )   dy   y′(t )   y′

 dt 
Here given vector is
1   4
X (t ) = X =   et +   tet
3   −4 
et + 4tet  e (1 + 4t ) 
t

X = t t
= t 
3e − 4te  e ( 3 − 4t ) 
Differentiating w.r.t. ' t ' ⇒
d t
d d  e t
(1 + 4t )  {
 dt e (1 + 4t ) } 
X=  t =
  
dt e ( 3 − 4t )   d t
dt
 dt {
e ( 3 − 4t ) } 

et (1 + 4t + 4 ) 
X′ =  t 
e ( 3 − 4t − 4 ) 
 4t + 5 
= et   ..................(2)
 −4t − 1

Now taking R.H .S . of (1) ⇒


1  e (1 + 4t ) 
t
2
AX =   
 −1 0  et ( 3 − 4t ) 
2 1  1 + 4t 
= et 
 −1 0  3 − 4t 
 2 + 8t + 3 − 4t 
= et  
 −1 − 4t 
 5 + 4t 
= et   ...............(3)
 −4t − 1 
1   4
From (2) & (3), we conclude that eq.(1) i.e. X ′ = AX shows its validity for given vector X =   et +   tet
3   −4 
⇒ X is solution of given system.

Hence the result.

Question 2
marks 10
1   2 8 
If the vectors ‘ X 1 =   et ’ and ‘ X 2 =   et +   tet ’ are the solutions of the system
 −1 6  −8 
X ′ = AX then determine whether these vectors form a fundamental set ∀t ∈ R by
investigating their linear independence.
Solution:
{ }
Two vectors solutions X 1 & X 2 form a fundamental set X 1 , X 2 if X 1 & X 2 are
linearly independent if Wronskian of X 1 & X 2 = W ( X 1 , X 2 ) ≠ 0 .
Thus we have to show that
( )
W X 1 , X 2 ≠ 0 for given vector solutions
 1  et 
X 1 =   et =  − t 
 −1 e 
 2  8  2et + 8tet 
X 2 =   et =   tet =  t t
6   −8  6e − 8te 
et (1 + 4t ) 
= 2 t 
e ( 3 − 4t ) 
Wronskian of
et 2et (1 + 4t )
X1 & X 2 = W ( X1 , X 2 ) = t
−e 2et ( 3 − 4t )
1 1 + 4t
= et .2 et = 2 et ( 3 − 4t + 1 + 4t ) = 8 e2t ≠ 0 ; ∀ t ∈ R
−1 3 − 4t
⇒ X 1 & X 2 are linearly independant.
⇒ X 1 & X 2 form a fundamental system.

Hence the result.


Question 3 marks 10

Solve the following system of differential equations


dx
= 4x + 5 y
dt
dy
= −2 x + 6 y
dt
Solution:
Given system is
dx
= 4x + 5 y
dt
it’s matrix form is
dy
= −2 x + 6 y
dt
 dx 
 dt   4 5  x 
 =
 dy   −2 6   y 
 dt 
d x  x 
⇒   = A 
dt  y   y
⇒ X ′ = AX ................(1)
 x(t )   4 5
where X =   , A= = coefficient of matrix
 y (t )   −2 6 
Characteristic equation of coefficient matrix
det ( A − I λ ) = 0
4−λ 5
=0
−2 6−λ
( 4 − λ )( 6 − λ ) + 10 = 0
⇒ ( λ − 6 )( λ − 4 ) + 10 = 0
λ 2 − 10λ + 24 + 10 = 0
λ 2 − 10λ + 34 = 0
10 ± 100 − 136 10 ± 6i
λ= = = 5 ± 3i which are Eigenvalues.
2 2
Eigen vector for λ1 = 5 + 3i is given by
 4 − ( 5 + 3i ) 5   k1 
( A − λ I ) k1 = 0 ⇒    =0
 −2 6 − ( 5 + 3i )   k2 
 −1 − 3i 5   k1  0 
⇒ =
 −2 − 1 − 3i   k2  0 
⇒ ( −1 − 3i ) k1 + 5k2 = 0 ..............(1)
−2k1 + (1 − 3i ) k2 = 0 ...................(2)
It has trivial solution (0, 0)
For nontrivial solution,

(1) ⇒ k2 =
( 3i + 1) k1
5
By inspection, taking k1 = 5
⇒ k2 = 3i + 1
5 
⇒ k1 =   i.e. 1st Eigen vector.
1 + 3i 
Eigen vector for λ2 = 5 − 3i given as
 4 − ( 5 − 3i ) 5 
( A − λ I ) k2 = 0 ⇒   k2 = 0
 −2 6 − ( 5 − 3i ) 
 −1 + 3i 5   k1 
⇒ =0
 −2 1 + 3i   k2 
⇒ ( −1 + 3i ) k1 + 5k2 = 0 ................(3)
− 2k1 + (1 + 3i ) k2 = 0.................(4)
Again (3) & (4) has trivial solution as (0, 0).For nontrivial solution
(4) ⇒ −2k1 + (1 + 3i ) k2 = 0

k1 =
(1 + 3i ) k2
2
By inspection taking k2 = 2 ⇒ k1 = 1 + 3i
1 + 3i 
∴ 2nd Eigen vector = k2 =  
2 
Consequently two solutions are
5  5 + 3i
X 1 = k1eλ1t =  e
1 + 3i 
1 + 3i  (5−3i ) t
X 2 = k2 eλ2t =  e
2 
By superposition principle general solution is
X = c1 X 1 + c2 X 2
5  1 + 3i 
X = c1e(5+3i ) t   + c2 e(5−3i ) t  
1 + 3i  2 
 x(t )  5c1e
(5+ 3i ) t
+ (1 + 3i ) c2 e(5−3i ) t 
 y (t )  =  
  c1 (1 + 3i ) e
(5+ 3i ) t
 + 2c2 e(5−3i ) t 

{
⇒ x(t ) = e5t 5c1e3i t + (1 + 3i ) c2e −3it }
and ⇒ y (t ) = e5t {c (1 + 3i ) e
1
3i t
}
+ 2c2 e−3it
Consider 5c1 = A , (1 + 3i ) c2 = B , (1 + 3i ) c1 = C , 2c2 = D
⇒ x(t ) = e5t  A {cos 3t + i sin 3t} + B {cos 3t − i sin 3t }
and ⇒ y (t ) = e5t C {cos 3t + i sin 3t } + D {cos 3t − i sin 3t }
∴ x(t ) = e5t [ c1 cos 3t + c2 sin 3t ]
and y (t ) = e5t [ c3 cos 3t + c4 sin 3t ] where c1 = A + B , c2 = i ( A − B ) , c3 = C + D , c4 = i ( C − D )

Hence the result.